2018 HES PRESIDENTIAL ADDRESS: FOLK WISDOM IN ECONOMICS. Issue 1 (March 2020) - Forget, Evelyn L.
Abstract : This article highlights the roles played by knowledge brokers in the history of economics. Knowledge creation is the joint product of teams of people engaged in parallel work. Economists do their professional work, whether that involves creating elaborate theories, gathering and interpreting data, or conducting experiments, all the while creating a variety of competing narratives about the economy. Economic agents go about their daily lives creating goods and services, caring for one another, saving and consuming, all the while making decisions based on whatever narratives they believe about how the economy functions. The various narratives between and among economists and economic agents create market opportunities for knowledge brokers, who sell their services to whoever will pay. They popularize economic insights in bestselling books, and work for think tanks or with various organizations, but they are also textbook writers, journal editors, and conference organizers, all of whom jointly contribute to the edifice of economic knowledge and facilitate communication. European beekeeping is used as an analogy.